2019
DOI: 10.1177/0300060519828945
|View full text |Cite
|
Sign up to set email alerts
|

Mollicutes antibiotic resistance profile and presence of genital abnormalities in couples attending an infertility clinic

Abstract: The present study aimed to identify Mollicutes infection in the reproductive system. We also examined the microbiological, biochemical, and antimicrobial profiles of Mollicutes infection, which are potentially associated with clinical reproductive abnormalities causing infertility in couples. Methods: Thirty-seven couples who were attending an infertility clinic were enrolled. Detection of genital mycoplasmas was performed in cervicovaginal samples or male urethral swabs. Microbiological culture and biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Lastly, after the inoculation of each of the domes, two or three drops of pure mineral oil were added. The gallery was incubated at 37°C, and the results were recorded at 24 and 48 hours [4,5].…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, after the inoculation of each of the domes, two or three drops of pure mineral oil were added. The gallery was incubated at 37°C, and the results were recorded at 24 and 48 hours [4,5].…”
Section: Methodsmentioning
confidence: 99%
“…The World Health Organization (WHO) defines clinical infertility as a condition of the reproductive system characterized by ‘the inability to achieve a clinical pregnancy after 12 months or more of regular unprotected sexual intercourse’, in the absence of any contraceptive methods ( 1 ). This condition, affecting one in seven couples, can be attributed to factors related to either the female, the male or both partners ( 1 , 2 ). The current paper does not cover any organic, hormonal or other external causes of infertility; the authors only scrutinized the infectious trigger.…”
Section: Introductionmentioning
confidence: 99%
“…In men, Ureaplasma is related to conditions such as urethritis, prostatitis, epididymitis and infertility. Studies have shown that both Ureaplasma and Mycoplasma hominis can negatively impact sperm quality ( 1 , 2 ). Reproductive tract infections can induce leukocytosis in semen, trigger the release of inflammatory factors and disrupt levels of reactive oxygen species (ROS), potentially resulting in vas deferens obstruction and subsequent infertility in men ( 1 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations